Association of interleukin-13 gene variants with susceptibility to brucellosis - Sayed-; Manoochehr Rasouli; Sohrab Najafipour; Ali Moravej; Mehdi Kalani; Manica Negahdaripour (Shiraz University of Medical Sciences, 2016)
Brucella is an intracellular Gram-negative bacterium. Previous reports showed that gene polymorphisms of cytokines can affect resistance or susceptibility to Brucella infection. Interleukin-13, a cytokine secreted by Th2 lymphocytes, has an important role in immune responses against established infections. In this study, we investigated the association of three polymorphic sites of IL-13 with susceptibility to brucellosis in Iranian population. In this study 169 patients with brucellosis and 71 healthy controls were included. DNA was extracted and genotyped for three bi-allelic polymorphisms of IL-13 gene at positions -1512A/C, -1055C/T, and +2044G/A by polymerase chain reaction-restriction fragment length polymorphism method. None of the studied alleles and genotypes of IL-13 gene (-1512A/C, -1055C/T, and +2044G/A) showed significant relationship with susceptibility to brucellosis. However, among eight haplotypes, the distribution of TCG and CAA haplotypes were significantly higher in the patients compared with those in the controls (P=0.002 and P=0.034, respectively). Although, the later did not tolerate Bonferroni correction. On the contrary, the distribution of TCA haplotype was higher in the controls compared to that in the patients (P=0.01). Furthermore, TAG/TCA haplogenotypes were significantly higher among controls compared to the brucellosis patients (P=0.025). P value resulted from TCA and TAG/TCA did not tolerate Bonferroni correction. There is no association between the inheritance of different alleles and genotypes of interleukin-13 gene and susceptibility to brucellosis. However, it seems that the inheritance of some haplotypes and haplogenotypes of IL-13 can impact the susceptibility to brucellosis.